2018
DOI: 10.1016/j.memsci.2018.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining membrane permeability during unsteady-state operation of anaerobic membrane bioreactors for municipal wastewater treatment following peak-flow

Abstract: Key highlights Peak flow characteristics (size, duration and frequency) are examined for AnMBR  Increasing gas flow rate during peak flow improves recovery  Supra-critical fluxes can be sustained for short durations  Specifying average flux below critical flux improves recoverability  Membrane area should be based on average flow, reducing capital cost AbstractIn this study, the impact of peak flow on anaerobic membrane bioreactor operation is investigated to establish how system perturbation induced by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…The TMP of AnMBRs is highly dependent on the critical flux and the sparging rate together with other environmental and operating conditions [35]. Furthermore, an initial flux below the critical flux, prior to the introduction of peak flow, is reported to be advantageous to permeability recovery [36]. In the study of Muñoz Sierra et al [18], increased salt concentration was found to affect the TMP negatively (350 mbar at a flux of 4.0 Lm 2. h -1 ).…”
Section: Effect Of Olr and High Salinity On Membrane Operationmentioning
confidence: 99%
“…The TMP of AnMBRs is highly dependent on the critical flux and the sparging rate together with other environmental and operating conditions [35]. Furthermore, an initial flux below the critical flux, prior to the introduction of peak flow, is reported to be advantageous to permeability recovery [36]. In the study of Muñoz Sierra et al [18], increased salt concentration was found to affect the TMP negatively (350 mbar at a flux of 4.0 Lm 2. h -1 ).…”
Section: Effect Of Olr and High Salinity On Membrane Operationmentioning
confidence: 99%
“…The granular 42.5 L reactor (G-AnMBR) was inoculated with 16 L granular sludge from a mesophilic UASB used for pulp and paper industry. Both inoculums had a previous acclimation of 3 years treating the same wastewater and had been left without feeding for 5 months (Wang et al, 2018b). During the previous acclimation period, the effect on membrane permeability of peak flow was assessed.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The impact of diurnal peak flow and stormwater flows on the permeability of MBR was investigated by Wang, Soares, Soares, Jefferson, and McAdam (2018) to determine if the design of the MBR surface area can be based on the average flows instead of the peak flows. A granular UASB (G‐UASB) AnMBR, pilot plant study, indicated that the membrane design could be based on average flows, and the membranes can be operated at peak.…”
Section: Fixed Film and Anaerobic Mbrmentioning
confidence: 99%